LINGUISTICS FEATURE IN INTRODUCTION SECTION WRITTEN BY LECTURERS ON JOURNAL SCIENTIFIC AND APPLIED INFORMATIC AND JOURNAL OF TECHNOPRENEURSHIP AND INFORMATION SYSTEM - Washlurachim Safitri; Halita Krisna Dayati (Teaching English and Language Learning English Journal, 2021)
The purposes of this research were known linguistics feature in introduction section written by lecturers on Journal Scientific and Applied Informatic and Journal of Technopreneurship and Informatin System. Linguistics feature by Wjiayanti [et.al] (2013) in Penulisan dan Penyajian Karya Ilmiah book : Konjungsi, kalimat aktif dan kalimat pasif. The reseacher found that in the lecturers’ introduction section on Journal Scientific and Applied Informatic and Journal of Technopreneurship and Informatin System were used linguistics feature by Wijayanti [et.al] (2013) in Penulisan dan Penyajian Karya Ilmiah book, namely konjungsi (dan, karena, sehinngga, oleh karena itu, and bahwa), kalimat aktif and kalimat pasif.Keywords       : Linguistics feature, introduction section.